Implementación de cribado de cardiopatía congénita neonatal con oximetría de pulso para valorar ecocardiografía neonatal precoz en el servicio de neonatología del Hospital Regional de Loreto - Villa Quiñones, Carolina Denise (2025)
Congenital heart defects are the leading cause of early neonatal mortality and the second leading cause of death in childhood. This project emphasizes the importance of early detection of congenital heart defects, noting that pulse oximetry is crucial for determining neonatal echocardiography, thus enabling the timely identification of these conditions. A consistency matrix is presented for a study on the implementation of neonatal screening for congenital heart defects through pulse oximetry and echocardiography at the Regional Hospital of Loreto. It includes variables, indicators, objectives, hypotheses, and methodological details such as population, techniques, instruments, and statistical analysis. It also describes the detection procedures, diagnostic criteria, and informed consent processes for patients. Furthermore, the project "Implementation of Neonatal Congenital Heart Defects Screening with Pulse Oximetry to Evaluate Early Neonatal Echocardiography at the Regional Hospital of Loreto" aims to assess the effectiveness of pulse oximetry screening in newborns for the early detection of congenital heart defects, comparing results with echocardiography and analyzing variables such as the prevalence of heart defects, pre- and postductal oxygen saturation values, and confirmed diagnoses. The study is based on international and national evidence demonstrating the usefulness of these techniques, emphasizing the importance of timely diagnosis to improve neonatal care. It is considered feasible due to access to reliable data and adequate resources. The objectives include determining the prevalence of congenital heart defects, evaluating oxygen saturation values, and identifying confirmed diagnoses, with a focus on improving early detection and neonatal care in Loreto.